Changes in plasma malondialdehyde concentration and some erythrocyte antioxidant enzymes in cows with prolapsus uteri, caesarean section, and retained placenta - Erisir, M; Akar, Y; Gurgoze, SY; Yuksel, M (Ecole Nationale Veterinaire Toulouse, 2006)
The periparturient period is especially critical for health and subsequent performance of dairy cows. The aim of the study was to detect the occurrence of an oxidative stress by the determination of the plasma malondialdehyde (MDA) concentration and the erythrocyte glutathione peroxidase (GSH-Px) and catalase (CAT) activities in cows with prolapsus uteri, caesarean section. and retained placenta. A total of 46 Holstein cows (15 cows with normal parturition, 15 cows with retained placenta. 8 cows with prolapsus uteri, 8 cows with caesarean section) of the Research and practice Farm of Firat University were used in this Study. CAT activity did not significantly vary in diseased animals (p > 0.05). while in cows with prolapsus uteri and caesarean section, plasma MDA concentrations significantly increased (p < 0.001). and GSH-Px activity was significantly lowered compared to the control group or to cows with retained placenta (p < 0.01). In retained placenta cows, plasma MDA concentrations and GSH-Px activity were not significantly altered although the enzyme activity tended to increase. These results Suggest that the antioxidant systems would be impaired and peroxidation reactions accelerated in cows with prolapsus uteri and caesarean section.
Keywords: malondialdehyde; glutathione peroxidase; catalase; cow-prolapsus uteri; retained placenta; caesarean section